ANALISIS PENERAPAN PENGENDALIAN KAS KECIL DI PT. PERTAMINA RETAIL SPBU COCO SLAMET RIYADI SAMARINDA - Heriyanto dan Firda Oktaviani (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study aims to analyze the suitability of the application of pettycash control at PT. Pertamina Retail SPBU COCO Slamet Riyadi Samarindawith elements of internal control according to theory.Internal control is a set of policies and procedures to protect companyassets or assets from all forms of misuse, ensure the availability of accuratebusiness accounting information, and ensure that management policies andregulations have been complied with or implemented properly by allcompany employees. The elements of internal control are the controlenvironment, risk assessment, control activities, information andcommunication, and monitoring.The collection technique used is (1) field research (field workresearch) using interviews and questionnaires. (2) library research bycollecting data on documentation and information at PT. Pertamina RetailSPBU COCO Slamet Riyadi Samarinda. The data analysis technique useddescriptive analysis, meanwhile, to determine the suitability with theelements of internal control using the Dean J. Champion calculationformula.Based on the results of research conducted on the application of pettycash control at PT. Pertamina Retail SPBU COCO Slamet Riyadi Samarindaby using a questionnaire for elements of internal control. From the results ofthe study using elements of internal control, namely the elements of thecontrol environment, risk assessment, control activities, information andcommunication and monitoring, the results are very appropriate. Inaddition, the petty cash flowchart systems and procedures are in accordancewith the elements of internal control. The calculation of internal controlusing the Dean J. Champion formula yields a result of 98.00% which meansit is very suitable. Based on the hypothesis proposed, namely the applicationof petty cash control at PT. Pertamina Retail SPBU COCO Slamet RiyadiSamarinda is not in accordance with the elements of internal controlaccording to the theory is rejected.The conclusion of this research is internal control on petty cash whichis implemented by PT. Pertamina Retail SPBU COCO Slamet RiyadiSamarinda is in accordance with the elements of internal control, so PT.Pertamina Retail SPBU COCO Slamet Riyadi Samarinda should continue tomaintain this condition so that the possibility of fraud and errors can beminimized.